Experience of participation in international projects in the aspect of interconnected processes (problems and prospects) – significance of the human factor - Garmash, Sergii (Національний технічний університет "Харківський політехнічний інститут", 2023)
The purpose of the work is to highlight the situation that has developed in higher educational institutions of Ukraine in terms of finding partners for participation in international projects; dynamic changes in the internal and external environments, which are components of the reasons for the decline of this direction; possible development prospects under certain conditions; the influence of the human factor on these processes. National Technical University “Kharkiv Polytechnic Institute” has sufficient experience of working in international projects. For its efficient international cooperation NTU “KhPI” was repeatedly recognized as one of the best universities both in the region and in Ukraine on the whole. The situation in finding partners to participate in international projects of general departments is difficult. That’s why, cooperation of general departments with special departments is necessary to involve the former in international projects. If earlier partnership proposals mostly came from foreign institutions, now the responsibilities of finding foreign partners for the institute's (department's) participation in international projects have been shifted to the shoulders of teachers. The direct officials subconsciously learned one of Andrew Carnegie's famous quotes: “The secret of success lies not in doing your own work, but in recognizing the right man to do it”. The unification of the higher education system with the standards of Western countries in recent years has led to the appearance of a whole wave of paper waste that increasingly fills the teacher's living space. But this is unlikely to trouble officials from education, who mainly pay attention to artificial ratings and redistribution of financial flows in this area. Obviously, at all levels, the phenomenon of “negative selection of power” is gaining momentum in all structural subdivisions of any organization, as it has already become an integral trend in Ukraine during the years of its independence, on a par with corruption, personal preferences and nepotism. In the conditions of modern challenges that the question of the competence of human resources is becoing increasingly acute. The ability to make informed decisions, to take responsibility, even simply to remain a decent person become guidelines in times of trials, when real leaders emerge and the real elite of society crystallizes.

Метою роботи є висвітлення ситуація, яка склалася у вищих навчальних закладах України з пошуку партнерів для участі у міжнародних проектах; динамічних змін у внутрішньому та зовнішньому середовищах, які є складовими елементами причини занепаду цього напрямку; можливих перспектив розвитку за певних умов; впливу людського чинника на зазначені процеси. Національний технічний університет «Харківський політехнічний інститут» має достатній досвід роботи в міжнародних проектах. За ефективну міжнародну співпрацю НТУ «ХПІ» неодноразово визнавався одним з кращих університетів як регіону, так і України в цілому. Складною є ситуація з пошуку партнерів для участі у міжнародних проектах загальних кафедр. Ось чому необхідна кооперація загальних кафедр зі спеціальними кафедрами для залучення перших до участі у міжнародних проектах. Якщо раніше пропозиції партнерства здебільшого надходили від зарубіжних інституцій, то зараз обов’язки з пошуку іноземних партнерів для участі інституту (кафедри) у міжнародних проектах перекладено на плечі викладачів. Безпосередні керівники на підсвідомості засвоїли один з висловів Ендрю Карнегі: «Секрет успіху полягає не в тому, щоб робити свою власну роботу, а в тому, щоб знайти кращу людину, яка зробить це краще за вас». Уніфікація системи вищої освіти зі стандартами західних країн за останні роки призвела до появи цілого валу паперового непотрібу, який все більше і більше заповнює життєвий простір викладача. Але це навряд чи бентежить функціонерів від освіти, які основну свою увагу приділяють штучним рейтингам та перерозподілу фінансових потоків у цій сфері. Вочевидь, що на всіх рівнях набирає обертів феномен «негативної селекції влади» в усіх структурних підрозділах будь-якої організації, оскільки це вже стало невід’ємним трендом в Україні за роки незалежності на рівні з корупцією, власними кишеньковими преференціями та непотизмом. В умовах сучасних викликів все гостріше постають питання компетентності людського ресурсу. Вміння приймати обґрунтовані рішення, брати на себе відповідальність, навіть просто залишатися порядною людиною становляться орієнтирами у часи випробувань, коли з’являються справжні лідери та викристалізовується справжня еліта суспільства.
Досвід участі у міжнародних проектах в аспекті взаємопов'язаних процесів (проблеми та перспективи) – значення людського чинника
Keywords: international projects; key performance indicators; cooperation of departments; negative selection of power; corruption; nepotism; real elite of society; міжнародні проекти; ключові показники ефективності; кооперація кафедр; негативна селекція влади; корупція; непотизм; справжня еліта суспільства